Involvement of Ceramide in Ischemic Tolerance Induced by Preconditioning with Sublethal Oxygen-Glucose Deprivation in Primary Cultured Cortical Neurons of Rats - Bhuiyan, Mohammad Iqbal Hossain; Islam, Mohammad Nurul; Jung, Seo Yun; Yoo, Hye Hyun; Lee, Yong Sup; Jin, Changbae (PHARMACEUTICAL SOC JAPAN, 2010)
The complex molecular cascades of ischemic tolerance in brain cells remain unclear. Recently, sphingolipid-related metabolite ceramide has been implicated as a second messenger in many biological functions, including neuronal survival and death. The present study, therefore, examined the roles of ceramide (Cer) in ischemic tolerance induced by preconditioning with sublethal oxygen-glucose deprivation (OGD) using primary cultured cortical neurons of rats. Preconditioning of the neurons with sublethal 1-h OGD produced robust neuroprotection against cell death induced by lethal 3-h OGD imposed 12 h after preconditioning when measured by the MTT assay. Analysis of sphingolipids using LC-MS/MS showed that the ischemic preconditioning resulted in significant increases in the levels of C-16:0 Cer, C-18:0 Cer, C-20:0 Cer, C-24:0 Cer, C-24:1 Cer and the total ceramide contents compared with the sham-washed control group. However, sphingomyelin contents were not significantly changed by the ischemic preconditioning, suggesting that ceramides were increased through the de novo synthetic pathway. In the case of severe OGD paradigm, levels of ceramide and sphingomyelin in the lethal OGD group were not significantly different from those of the control group or the lethal OGD group with preconditioning at any time points studied. Treatment with an inhibitor of de novo ceramide synthesis, fumonisin B-1, during the ischemic preconditioning period completely blocked preconditioning-induced ischemic tolerance. Moreover, application of a non-cytotoxic concentration of exogenous cell-permeable ceramide produced neuroprotection against lethal OGD. The results suggest that ceramides increased by sublethal OGD preconditioning play an important role in induction of ischemic tolerance.
Keywords: PROGRAMMED CELL-DEATH; TNF-ALPHA; HIPPOCAMPAL-NEURONS; INDUCED APOPTOSIS; CEREBRAL-CORTEX; SURVIVAL; GROWTH; BRAIN; SPHINGOSINE; GENERATION